A STUDY OF A COMMON QUINCE (CYDONIA OBLONGA) LEAF INFUSION IN A CHRONIC EXPERIMENT (Journal of Universal Science Research, 2025)
To study the chronic toxicity of a quince leaf infusion (1:10) in albino rats.